Un prosímetro panegírico de Cristóbal Mosquera de Figueroa: el Elogio al retrato de don Álvaro de Bazán - J. Ignacio Díez (Criticón, 2018)
In the Breve compendio de disciplina militar, by Cristóbal Mosquera de Figueroa, there is a Elogio al retrato de don Álvaro de Bazán as the culmination of an apparently miscellaneous book. The praise is entrusted to the unusual mixture of prose and verse. With the prosimeter the author, judicial counselor and poet, shows a refined use of historical and literary values to compose a rigorous praise with true facts and to immortalize a heroic life through the word.